Effect of urea super granule and prilled urea on the growth and yield of broccoli - Hussain, MJ; Karim, AJMS; Islam, MS; Rahman, M (Bangladesh Journal of Agricultural Research, 2018)
A field experiment was conducted at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during the period from 2012-13 to verify the effectiveness of urea super granule (USG) and prilled urea (PU)on growth, yield and yield attributes of broccoli in Shallow Red-Brown Terrace Soil under Madhupur Tract (AEZ-28). The experiment was laid out in a Randomized Complete Block Design with three replications having 5 treatments constituted with different levels of USG and PU as- T1: Control, T2: USG-N140 (140 kg N as USG), T3: USG-N160 (160 kg N as USG), T4: USG-N180 (180 kg N as USG), T5: PU-N180 (180 kg N as PU). Performance of USG was better than PU and the treatment USG-N160 gave the highest yield (13.49 ton ha-1) which was followed by USG-N180 (12.43 ton ha-1) and PU-N180(12.05 ton ha-1) having significant difference among these. Higher but statistically identical number of lateral head 5.103 and 5.38 was produced by USG-N160 and USG-N180 treatments, respectively in comparison with PU-N180 (5.04). But higher lateral head yields (6.05 and 5.03 ton ha-1) were found in USG-N180 treatments followed by PU-N180. All the yield contributing characters and the economic profitability were favorably correlated with these high yield performing treatments with the highest MRR (3336.67%) obtained from USG-N160 which indicated that USG @ 160 kg N ha-1 (USG-N160) is the most economically viable N dose in terms of yield and economics for broccoli production. Therefore, USG @ 160 kg N ha-1 (USG-N160) with other recommended fertilizer could be suggested as USG based fertilizer recommendation for better broccoli production in terms of yield and economics in Silty Clay Loam Soil of Madhupur Tract. Bangladesh J. Agril. Res. 43(1): 53-69, March 2018